2014
DOI: 10.1371/journal.pone.0090245
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Induced Functional Recovery after Peripheral Nerve Repair Is Associated with Increased Levels of Neurotrophic Factors

Abstract: Benefits of exercise on nerve regeneration and functional recovery have been reported in both central and peripheral nervous system disease models. However, underlying molecular mechanisms of enhanced regeneration and improved functional outcomes are less understood. We used a peripheral nerve regeneration model that has a good correlation between functional outcomes and number of motor axons that regenerate to evaluate the impact of treadmill exercise. In this model, the median nerve was transected and repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 27 publications
3
72
0
1
Order By: Relevance
“…These findings thus extend on previous studies showing that PGC1α remodels the NMJ [55,56], and also converts muscle fibers from a fast to slow subtype [55]. Additionally, exercise boosts production of a number of local and systemic growth factors that have positive benefits on aging muscles and NMJs, including insulin like growth factor-1 (IGF1), brain derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) [57,58]. …”
Section: Lifestyle and Molecular Factors That Preserve The Nmj Intsupporting
confidence: 76%
“…These findings thus extend on previous studies showing that PGC1α remodels the NMJ [55,56], and also converts muscle fibers from a fast to slow subtype [55]. Additionally, exercise boosts production of a number of local and systemic growth factors that have positive benefits on aging muscles and NMJs, including insulin like growth factor-1 (IGF1), brain derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) [57,58]. …”
Section: Lifestyle and Molecular Factors That Preserve The Nmj Intsupporting
confidence: 76%
“…For instance, Cote and colleagues showed that recovery of H-reflex frequency-dependent depression in rats was correlated with the increase in BDNF resulting from step- and bike-training (8). Improved functional recovery after PNI involving the forelimb in mice was recently reported from the Hoke laboratory (24). Not only did CT treadmill exercise like ours improve recovery of forelimb grip function, the improvement was also correlated with an increase in BDNF in both the nerves and the serum.…”
Section: The Effects Of Exercise Extend Beyond Axon Regeneration To Fmentioning
confidence: 71%
“…The implication of these findings is that people with the Val66Met SNP might not respond to exercise training that is thought to improve recovery from PNI. For example, if the correlations found between functional improvement and increased BDNF found in rodent models (for PNI (24) and for SCI (8)) hold up for humans, then we would expect a diminished or null effect of exercise after PNI for people with the Val66Met SNP. Therefore, the parameters of rehabilitation exercise that improve functional recovery in these people might be drastically different.…”
Section: What Do These Results Mean For People With Pni's?mentioning
confidence: 99%
“…This seems to indicate that exercise can enhance nerve regeneration via mechanisms other than (or in addition to) improving glycaemic control . Low‐level treadmill exercise training (10 m/min, 1‐2 h/d, 5 d/wk, 4‐10 wk) in healthy mice with transected peripheral nerves induced axonal regeneration and functional recovery . The exercise‐trained mice had a higher number and larger size of regenerated axons, more mature myelination, and muscle hypertrophy than the mice with transected nerves that did no exercise .…”
Section: Discussionmentioning
confidence: 98%